Plk1 inhibition enhances the efficacy of androgen signaling blockade in castration-resistant prostate cancer - Zhang, Zhe (Cancer Res, 2014)
Prostate cancer (PCa) is thought to be driven by oxidative stress, lipid metabolism, androgen receptor (AR) signaling and activation of the PI3K/AKT/mTOR pathway, but it is uncertain how they may become coordinated during progression to castration-resistant disease which remains incurable. The mitotic kinase polo-like kinase 1 (Plk1) is elevated in PCa where its expression is linked to tumor grade. Notably, Plk1 signaling and lipid metabolism were identified recently as two of the top five most upregulated pathways in a mouse xenograft model of human PCa. Herein, we show that oxidative stress activates both the PI3K/AKT/mTOR pathway and AR signaling in a Plk1-dependent manner in prostate cells. Inhibition of the PI3K/AKT/mTOR pathway prevented oxidative stress-induced activation of AR signaling. Plk1 modulation also affected cholesterol ester accumulation in PCa via the SREBP pathway. Lastly, Plk1 inhibition enhanced cellular responses to androgen signaling inhibitors (ASI) and overcame ASI resistance in both cultured PCa cells and patient-derived tumor xenografts. Given that activation of AR signaling and the PI3K/AKT/mTOR pathway is sufficient to elevate SREBP-dependent expression of key lipid biosynthesis enzymes in castration-resistant PCa, our findings argued that Plk1 activation was responsible for coordinating and driving these processes to promote and sustain the development of this advanced stage of disease. Overall, our results offer a strong mechanistic rationale to evaluate Plk1 inhibitors in combination drug trials to enhance the efficacy of androgen signaling inhibitors in castration-resistant prostate cancer.